Pengaruh Pendapatan Asli Daerah Terhadap Belanja Daerah Kota Makassar - Dahlia Baharuddin (Jurnal Mirai Management, 2022)
The ability of the region to manage regional original income can be used as the basic capital of regional government in financing regional development and businesses. This study aims to empirically examine the effect of Regional Original Income on Makassar City Regional Expenditures from 2010 to 2019. This type of research is quantitative research, using secondary data in the form of time series data on the Realization of Regional Original Income and Regional Expenditures for Makassar City for the 2010-2019 observation period. The research method uses descriptive analysis, simple linear regression with the ordinary least square (OLS) method, partial test, and test of determination with the help of SPSS version 25 software. The results of this study indicate that the Regional Original Income has a positive and significant effect on the Makassar City Regional Expenditure. Keywords: Regional Original Income, Regional Expenditure